2022
DOI: 10.1101/2022.11.07.515431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering circuits of human iPSC-derived neurons and rat primary glia

Abstract: Novel in vitro platforms based on human neurons are needed to improve early drug testing and address the stalling drug discovery in neurological disorders. Topologically controlled circuits of human induced pluripotent stem cell (iPSC)-derived neurons have the potential to become such a testing system. In this work, we build in vitro co-cultured circuits of human iPSC-derived neurons and rat primary glial cells using microfabricated polydimethylsiloxane (PDMS) structures on microelectrode arrays (MEAs). Such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The field of bottom-up neuroscience[10] has profited from the ever-increasing quality of new 3D printing and microfluidic tools. By now such devices can be used to control axonal growth with high fidelity in neuronal cultures [11, 12] even with highly sensitive cells such as human-induced pluripotent stem cell (hiPSC)-derived neurons [13, 14]. While these approaches introduce a high level of control to the cultures themselves, such control is only useful, if interaction with such cell cultures occurs in a reliable fashion for extended periods of time.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The field of bottom-up neuroscience[10] has profited from the ever-increasing quality of new 3D printing and microfluidic tools. By now such devices can be used to control axonal growth with high fidelity in neuronal cultures [11, 12] even with highly sensitive cells such as human-induced pluripotent stem cell (hiPSC)-derived neurons [13, 14]. While these approaches introduce a high level of control to the cultures themselves, such control is only useful, if interaction with such cell cultures occurs in a reliable fashion for extended periods of time.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The guidance of axons within microstructures is based on the axonal edge guidance phenomenon (Renault et al, 2016). Using polydimethylsiloxane (PDMS) microstructures it was previously shown that engineered neural networks could be established on standard, low-density glass-based MEAs using both primary rat neurons (Ihle et al, 2022;Forró et al, 2018;Mateus et al, 2022) as well as hiPSC-derived neurons (Girardin et al, 2022a(Girardin et al, , 2022b. More recently, we have transferred this 'bottom-up' neuroscience technique to complementary metal-oxide-semiconductor (CMOS)-based MEAs, which offer electrode densities orders of magnitude larger than in conventional passive MEAs and reveal the propagation of spontaneous activity in such small, confined neural networks with high spatiotemporal resolution (Duru et al, 2022).…”
Section: Introductionmentioning
confidence: 99%